Vegetarian or vegan interest in purchasing meat-like hamburgers (Research, Society and Development, 2021)
The option to become vegetarian or vegan has increased significantly in recent years, thus, the objective of this work was to investigate whether the vegetarian or vegan public is interested in purchasing meat-like hamburgers, such as vegetable-based ones, or if on the contrary, these products cause revulsion. An individual electronic questionnaire was applied, in which participants were asked to provide personal information and answer questions related to their choice of food. The 136 respondents were mostly female, in between 18 and 33 years old. It was noticed that the majority did not show disgust, and many have already even tasted and liked it, considering it as an alternative food, as long as fair prices were charged, that is, similar to meat products. The reasons cited as for why participants adopted a vegetarian or vegan diet were mostly in respect for animals, followed by respect for the environment. When analyzing the responses, it was evident that there is no repulsion for a product similar to beef, such as a vegetable-based hamburger and, therefore, there is a perception of the search for varied products and the interest in being an alternative food with potential for sale.